GWO-Based Optimal Tuning of Type-1 and Type-2 Fuzzy Controllers for Electromagnetic Actuated Clutch Systems. Issue 4 (2021) - Bojan-Dragos, Claudia-Adina; Precup, Radu-Emil; Preitl, Stefan; Roman, Raul-Cristian; Hedrea, Elena-Lorena; Szedlak-Stinean, Alexandra-Iulia
Abstract: The goal of this paper is to develop the optimal fuzzy controllers for nonlinear processed represented by electromagnetic actuated clutch systems in order to improve the control system performance. A Takagi-Sugeno type-1 fuzzy logic controller and a Takagi-Sugeno type-2 fuzzy logic controller are designed here to enhance position tracking performance of electromagnetic actuated clutch systems, which are subjected to parametric uncertainties. The parameters of membership functions and the rules of the proposed fuzzy controllers are optimally tuned using a recent metaheuristic optimization algorithm, namely the Grey Wolf Optimizer. A comparison of Takagi-Sugeno type-1 and Takagi-Sugeno type-2 fuzzy control systems is carried out in various simulation scenarios, which are discussed and analyzed. The results highlight that the type-2 fuzzy controller performs efficiently for these complex processes.